2007
DOI: 10.1007/s10592-007-9415-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the conservation status of the land snail Oreohelix peripherica wasatchensis (Family Oreohelicidae)

Abstract: Establishing conservation priorities for invertebrate groups has proven difficult as many proposed units of diversity are based on morphological features that do not reflect evolutionary history. This confusion is confounded by poorly defined ranges of proposed endemic and endangered groups, leading to problems formulating adequate conservation management strategies. We examined one such group, Oreohelix peripherica wasatchensis, a landsnail located in the Wasatch Front Range of Utah that is a candidate for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A key initial task in animal conservation is to delimit monophyletic lineages of organisms and determine the geographic extent of those lineages. Delimiting lineages is especially important for many invertebrates groups where traditional alpha taxonomy has proven to be a poor representation of actual diversity (Emberton, 1995;Guralnick, 2005;Pfenninger, Cordellier & Streit, 2006;Weaver et al, 2008). Accurate range data is equally important because many initial animal conservation decisions are made based in part on the presumed geographical extent of occupancy of a lineage, which itself determines extent of habitat occupied (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key initial task in animal conservation is to delimit monophyletic lineages of organisms and determine the geographic extent of those lineages. Delimiting lineages is especially important for many invertebrates groups where traditional alpha taxonomy has proven to be a poor representation of actual diversity (Emberton, 1995;Guralnick, 2005;Pfenninger, Cordellier & Streit, 2006;Weaver et al, 2008). Accurate range data is equally important because many initial animal conservation decisions are made based in part on the presumed geographical extent of occupancy of a lineage, which itself determines extent of habitat occupied (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For groups where sampling has been sporadic and taxonomic expertise is limited, the distribution, and often presumed endemicity, is not always accurately known. One approach in groups where taxonomic identification is difficult and range extent has yet to be properly determined is to examine variation in presumed neutral genetic markers from multiple individuals sampled broadly across a region, including those populations thought to be of conservation concern (Weaver et al, 2008). The resulting phylogenetic analysis can not only help document lineages and range extents of those lineages, but can also provide useful information about past and current events that lead to lineage diversifications through an assessment of the amount of genetic differentiation among lineages (Sites & Crandall, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…that other species of the Oreohelix genus (e.g., Black Hills Mountainsnail [Oreohelix cooperi]) are already being listed as 'threatened' at the state level, and local collectors have observed that the Rocky Mountainsnail is rapidly declining (while once common and widespread across the Colorado Front Range in the early 1900s, few populations remain) [71,72]. Many populations exist only within certain geographically isolated rocky outcrops or canyons, which may in turn make their gut microbiomes equally as specialized [73]. For such species and subspecies, captive-breeding programs may be important for ensuring species survival, by supplementing wild populations or creating "backup" populations.…”
Section: Plos Onementioning
confidence: 99%
“…The ecological specialization of these snails to small islands of limestone in montane ecosystems makes them vulnerable to extirpation, and many species are considered endangered or highly threatened by the International Union for Conservation of Nature and Natural Resources (IUCN; https://www.iucnredlist.org/) and local state governments. However, conservation officials are hesitant to develop conservation plans for many Oreohelix species, as recent genetic studies indicate that there is a lack of phylogenetic evidence for many existing taxonomic units (3) and the possible existence of cryptic species (4). These findings suggest that our understanding of oreohelicid diversity is limited and highlight the need for genomic resources to unravel species relationships in this group so that conservation plans can be developed based on robust species relationships.…”
Section: Announcementmentioning
confidence: 99%